Expanding and characterizing esophageal epithelial cells obtained from children with eosinophilic esophagitis. (August 2018) - Sayej, Wael; Foster, Christopher; Jensen, Todd; Chatfield, Sydney; Finck, Christine
Abstract Background The role of epithelial cells in eosinophilic esophagitis (EoE) is not well understood. In this study, our aim was to isolate, culture, and expand esophageal epithelial cells obtained from patients with or without EoE and characterize differences observed over time in culture. Methods Biopsies were obtained at the time of endoscopy from children with EoE or suspected to have EoE. We established patient-derived esophageal epithelial cell (PDEEC) lines utilizing conditional reprogramming methods. We determined integrin profiles, gene expression, MHC class II expression, and reactivity to antigen stimulation. Results The PDEECs were found to maintain their phenotype over several passages. There were differences in integrin profiles and gene expression levels in EoE-Active compared to normal controls and EoE-Remission patients. Once stimulated with antigens, PDEECs express MHC class II molecules on their surface, and when co-cultured with autologous T-cells, there is increased IL-6 and TNF-α secretion in EoE-Active patients vs. controls. Conclusion We are able to isolate, culture, and expand esophageal epithelial cells from pediatric patients with and without EoE. Once stimulated with antigens, these cells express MHC class II molecules and behave as non-professional antigen-presenting cells. This method will help us in developing an ex vivo, individualized, patient-specific model for diagnostic testing for causative antigens.